Permian–Triassic Boundary in Sedimentary Succession of the Barents Sea - Malysheva, E.O.; Doronina, M.S.; Kleschina, L.N.; Nikitina, V.A.; Popov, A.S.; Vasilyeva, N. (Russian geology and geophysics, 2024)
—The Permian–Triassic (P–T) boundary records the most dramatic events in Phanerozoic history. The character of the boundary differs greatly, so it has been the subject of great discussion. The Barents Sea separates regions having markedly different expressions of the P–T boundary, and it can give an insight into the conditions of formation of this boundary in different parts of the European North. This contribution is based on a combination of regional projects from the Russian and Norwegian sectors, including seismic data across the Barents Sea and well data in marginal zones. Application of new seismic data and the sequence stratigraphy concept provides a novel approach to correlation and interpretation of the P–T boundary beneath the Barents Sea. The study has revealed a distinct regional sequence boundary corresponding to the P–T boundary with conformable and unconformable bedding. Three major types of this stratigraphic boundary are recognized. The distinct “erosional” type of the P–T boundary, with a significantly reduced Permian section, exists in the southeast (Timan–Pechora Basin). The conformable “overcompensated” type of boundary with an additional Lower Triassic section is interpreted in the central part of the Barents Sea. Westward, beneath the Norwegian sector, a relatively conformable “condensed” type of P–T boundary predominates. In addition to these types associated with regional paleostructural and depositional trends, the superposed “structural” subtype caused by local growth of structures at the Permian–Triassic boundary is identified.